Entrepreneurial Education And Readiness: A Bibliometric Analysis - Ambarita, Nita; Suwatno, Suwatno (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2024)
This study aims to determine the trend of previous research on how entrepreneurship education affects entrepreneurial readiness in universities and make recommendations for future research directions. The research method used descriptive bibliometric analysis. Based on the results of data retrieved from the Scopus database, 76 recent scientific articles are used in this review which are then converted into RIS format and processed with VOSviewer. The main findings of this study are: (1) research related to entrepreneurship education and entrepreneurial readiness emerged in 1997 and experienced rapid development in the last decade; (2) the number of authors, institutions, and countries producing research in this field is still very limited; (3) research collaboration has not been significantly established; (4) the most productive journals in this field are Industry and Higher Education and International Journal of Entrepreneurial Behaviour and Research; (5) there are five common themes discussed in the literature on entrepreneurship education and entrepreneurial readiness over the last 26 years; entrepreneurship education and learning in higher education; the effect of entrepreneurship education on entrepreneurial readiness; entrepreneurship learning methods; and entrepreneurship. The findings are discussed and the authors conclude by proposing possible avenues for future research.